(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This paper will focus on instrumental versions (kuis) related to ritual themes. In the spotlight: 1. Types of notices and farewells to the dead in Kazakh musical folklore. Brief description; 2) Their representation in folk instrumental music. In the musical tradition of the Kazakhs, a whole complex of phenomena has been formed, one way or another connected with the rituals of farewell (death). Among them are yestirtu (the custom of an allegorical message about death), zhoktau (crying, lamentation, mourning for the deceased), zarlau (bitter crying, sobbing), koshtasu (farewell), arnau (dedication) to zhubatu (consolation), konil aitu (consolation song). In instrumental music, there are pieces of a program nature created for the death of famous people. They are performed on various musical instruments (dombra, kyl-kobyz and sybyzgy). Some of them belong to the so-called kuis-legends (anyz–kuyler), others have a history of their creation. The author shows the features of instrumental yestirtu using the examples of several kuis: folk “Aksak kulan”, “Salyk olgen”of Dauletkerei, cycle “Tort (four) tolgau” of Toka (dombra), “Yerden” of Ikhlas (kobyz), “Arbiyanyn konyry” (sybyzgy). Many of the motifs used in the kuis of the memory of the dead are based on certain words. They can have subtexts, which also reveals their connection with the song zhoktau (see “Aksak kulan”, “Salyk Olgen”, “Erden” etc.). In the instrumental tradition of the Kazakhs, there are cyclic pieces associated with zhoktau (see “Tort (four) Tolgau” of Toka). In addition, as instrumental versions, these pieces can be performed independently, outside of ritual actions. Therefore, they have been preserved and today adorn the repertoire of many modern Kazakh dombra players.